Literasi Keuangan, Perilaku Keuangan, dan Pendapatan Terhadap Keputusan Investasi pada Mahasiswa Akuntansi Udinus - Aisyah Amalia Al-Aziz; Ira Septriana; Ngurah Pandji Mertha Agung Durya; Melati Oktafiyani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of financial literacy, financial behavior, and income on the investment decisions of undergraduate accounting students at Dian Nuswantoro University. The background of this study is based on the increasing trend of investment among Gen Z and various findings from previous studies on the factors that influence investment decisions. This study employs a quantitative approach using a survey method via a questionnaire administered to 92 respondents selected through stratified random sampling. Data were analyzed using multiple linear regression analysis with the assistance of SPSS 27. The results indicate that financial behavior and income have a positive and significant influence on investment decisions, while financial literacy does not have a significant influence. These findings confirm that attitudes and actual financial conditions play a more dominant role in shaping students' investment decisions than their level of financial knowledge. This study has important implications for financial education and the promotion of healthy financial behavior among students.